2019
DOI: 10.1080/17461391.2019.1674927
|View full text |Cite
|
Sign up to set email alerts
|

The effect of arm‐crank exercise training on power output, spirometric and cardiac function and level of autonomy in persons with tetraplegia

Abstract: Studies on the effects of exercise training in persons with cervical spinal cord injury (CSCI) are scarce. The aim of this study was to determine the effect of an 8-week stationary arm-crank exercise (ACE) training programme on the level of autonomy, exercise performance, pulmonary functional parameters and resting heart rate variability (HRV) in persons with CSCI. Quadriplegia Index of Function (QIF), arm-crank peak power output (Ppeak), spirometric variables, and HRV indices were measured before and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Lastly, aerobic capacity gains were greatest in the first three months of training. It is possible that participants reached a plateau in aerobic capacity after three months of FESRT and encountered physiological barriers, due to muscle,( 39 ) cardiac,( 40 ) or to ventilatory limits. ( 1 , 26 , 40 ) For example, Qui and colleagues previously reported that after several months of FES rowing, training-related increases in peak aerobic capacity were markedly dependent on peak ventilation in those with high-level SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, aerobic capacity gains were greatest in the first three months of training. It is possible that participants reached a plateau in aerobic capacity after three months of FESRT and encountered physiological barriers, due to muscle,( 39 ) cardiac,( 40 ) or to ventilatory limits. ( 1 , 26 , 40 ) For example, Qui and colleagues previously reported that after several months of FES rowing, training-related increases in peak aerobic capacity were markedly dependent on peak ventilation in those with high-level SCI.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that participants reached a plateau in aerobic capacity after three months of FESRT and encountered physiological barriers, due to muscle,( 39 ) cardiac,( 40 ) or to ventilatory limits. ( 1 , 26 , 40 ) For example, Qui and colleagues previously reported that after several months of FES rowing, training-related increases in peak aerobic capacity were markedly dependent on peak ventilation in those with high-level SCI. ( 26 ) Improvements in muscle metabolism and/or cardiovascular function after FESRT may outstrip the pulmonary system’s ability to generate greater ventilation, and Vivodtzev and colleagues showed that ventilatory support can reverse both VE peak and VO 2peak limitations in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, given its physiological and biomechanical benefits, handcycling is also suitable as a safe training mode to regain and maintain fitness [7,62,[64][65][66][67][68][69][70][71][72]. It is also possible to safely train patients who have a very low physical capacity for instance due to a high cervical spinal cord lesion [73][74][75] or because they are at the early start of rehabilitation [6,67,76,77]. Especially for those who are undertrained or those with a relatively high body mass in relation to their available active arm muscle mass, arm crank ergometers can be useful to be able to start training at a very low power output level [74,75].…”
Section: Health Benefitsmentioning
confidence: 99%
“…Within an experimental set-up a crank axis height at acromion/shoulder level is often used or recommended [43,133,177]. In practice, however, an even lower setting is used; the crank axis height at mid-sternum is often seen, especially with "bullhorn" cranks [75,76,81].…”
Section: Synchronous Versus Asynchronous Synchronous Handcycling Wasmentioning
confidence: 99%
“…Handcycling is a popular form of outdoor propulsion for persons who are dependent on their upper body for locomotion during and after rehabilitation (Kraaijenbrink et al, 2020b ). To practice or test handcycle performance, the arm crank ergometer is often used as an indoor alternative, especially in early rehabilitation (Krops et al, 2017 ; Kouwijzer et al, 2018b ; Bresnahan et al, 2019 ; Williams et al, 2019 ; Brizuela et al, 2020 ). Outdoor handcycling requires steering, hence the front wheel and fork must rotate freely around the steering axis.…”
Section: Introductionmentioning
confidence: 99%